PENGARUH KOMPETENSI, PENGALAMAN KERJA DAN DISIPLIN KERJA TERHADAP PENGEMBANGAN KARIR KARYAWAN - Diasana, I Gede Arya Pradnya; Suwandana, I Gusti Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study is to explain the effect of competence, work experience and work discipline on the career development of employees of PT. Dwipayana Sumber Rejeki. This research was conducted at PT. Dwipayana Sumber Rejeki. The number of samples used is 50 employees, with the method of determining the saturated sample. The data was collected using a questionnaire, the data was analyzed using multiple linear regression analysis techniques. In this research, the theory used is Personality and Behavior Theory. The results of this study indicate that competence has a positive and significant effect on the career development of employees of PT. Dwipayana Sumber Rejeki. Work experience has a positive and significant effect on the career development of employees of PT. Dwipayana Sumber Rejeki. Work discipline has a positive and significant effect on the career development of PT. Dwipayana Sumber Rejeki. The theoretical implications of this research can provide evidence on the development of human resource management science that is able to explain the theoretical model used as a basis in formulating hypotheses, namely the influence of competence, work experience and work discipline on employee career development which is able to empirically prove the theory used in This research is personality and behavior theory